Artifak : cultural revival, tourism, and the recrafting of history in Vanuatu - DeBlock, Hugo (Berghahn Books, 2018)
In Vanuatu, commoditization and revitalization of culture and the arts do not necessarily work against each other; both revolve around value formation and the authentication of things. This book investigates the meaning and value of (art) objects as commodities in differing states of transit and transition: in the local place, on the market, in the museum. It provides an ethnographic account of commoditization in a context of revitalization of culture and the arts in Vanuatu, and the issues this generates, such as authentication of actions and things, indigenized copyright, and kastom disputes over ownership and the nature of kastom itself.